Thyrotoxic periodic paralysis: an unusual presentation of weakness. Issue 5 (3rd September 2003) - Paul, B; Hirudayaraj, P; Baig, M W
Abstract : Thyrotoxic periodic paralysis is a rare endocrine disorder seen predominantly in men of Asian origin. The case is reported of a patient who presented to the accident and emergency department with sudden onset of weakness of his lower limbs. Hypokalaemia was identified and treated with resolution of symptoms. Additional tests identified the patient as being thyrotoxic. He was treated with oral antithyroid drugs. It is important to consider the diagnosis of thyrotoxic periodic paralysis in patients presenting with acute onset of weakness. The report discusses the epidemiology, presentation, treatment, and complications of this condition.